Evaluating the Quality of Banking Assets and Its Impact on The market Value of the Stock (Survey Study on conventional Banks Listed in Damascus Stock Market) - انجرو ايمان (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The study aimed to evaluate the asset quality of conventional Banks Listed in Damascus Stock Market, and to study the impact of its asset quality on the market value of the shares of these banks. The data collection of financial reports for conventional Banks Listed in Damascus Stock Market during the period from 2016 to 2021. Panel data approach was employed in order to analyze data. The results showed that conventional Banks Listed in Damascus Stock Market have a good level of assets. And the asset quality (which it measured by Loan Loss Provision) has a statistically significant negative effect on the market value of the stock. The researcher believes that the reason behind the negative effect is that a higher provision ratio means lower quality assets. To be concluded, that the quality of assets of conventional Banks Listed in Damascus Stock Market has a statistically significant on the market value of the stock.